Development of an early weaning program for dairy calves - Morrill, J.L.; Dayton, A.D.; Zmolek, A.J.; Vitcenda, M.A. (Kansas Agricultural Experiment Station, 2012)
After preliminary experiments, four trials were conducted to develop and test a new feeding program for calves. The program involves the use of a special feed (a prestarter) to encourage calves to eat dry feed and to provide high quality nutrients during the time of initial rumen development. Using this plan, calves were weaned at 2 weeks of age with good results.
Keywords: Dairy; Weaning; Gain; Intake